Environmental applications of geophysical surveying techniques - Gibson, Paul J. (Paul Jude), 1954-; Gibson, Paul J.; George, Dorothy M. (New York : Nova Publishers, 2013)
Geophysical techniques provide useful information about the subsurface with suitable techniques chosen for particular environments or problems. Thus resistivity would be considered more useful than gravity for the detection of contaminant plumes whereas gravity is ideal for the detection of cavities. There are two major advantages in adopting a geophysical approach to studying the subsurface: the non-destructive and very cost-effective nature of most geophysical surveys. This book should be of great benefit to undergraduate and postgraduate students who are taking geology or geophysics courses. It is also aimed at a wider audience, those who need to know what exists below the surface and those to whom the state of that subsurface, and hence to a large extent our environmental well being, is important. Geophysics is a science that transcends the usual disciplinary boundaries, so this book will also be beneficial for engineers, geologists, planners, archaeologists, hydrologists, geographers and environmental scientists. Equations in this book are restricted to those that are essential to provide a better understanding of a particular technique or specific theoretical concept. High school mathematics is all that is required to comprehend their use.
7. Seismic geophysical techniques ; Introduction -- Theoretical concepts -- Seismic surveying equipment -- Noise on seismic surveys -- Seismic wave refraction -- Considerations for seismic refraction surveys -- Seismic wave reflection -- Applications of seismic surveys -- 8. Other geophysical techniques employed in environmental studies ; Introduction -- Radiometric surveys -- Radiometric surveying -- Magnetotelluric surveys -- Borehole logging -- Logging methodology -- Spontaneous potential (SP) log -- Cross-hole measurements.
Includes bibliographical references (pages 345-352) and index.
Description based on print version record and CIP data provided by publisher.
English.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Geophysics -- Technique; Geophysics -- Environmental aspects; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Geophysics -- Environmental aspects; Geophysics -- Technique; Electronic books; Electronic books